Hubungan Pengetahuan dan Sikap Ibu Hamil dengan Anemia terhadap Kepatuhan dalam Mengonsumsi Tablet Tambah Darah (Fe) di Puskesmas Olak Kemang Kota Jambi - Susilawati, Susilawati; Nadya, Embun (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2024)
Anemia is one of the global health problems. The prevalence of anemia in pregnancy varies, depending on socio-economic conditions, lifestyle, diet, and different attitudes and behaviors. Prevention by consuming blood-added tablets (Fe) regularly and consuming lots of green vegetables. This study aims to determine the relationship between knowledge and attitudes of anemia pregnant women towards compliance in consuming blood-added tablets (Fe). The research design used is quantitative research using a cross-sectional study design approach. The results showed that there was a relationship between knowledge of anemia in pregnant women to compliance in consuming blood-added tablets (Fe) at the Olak Kemang Puskesmas in Jambi City with a value of 0.004 (p <0.05) Add blood (Fe) at the Olak Kemang Puskesmas Jambi City with a value of p- value of 0,000 (p <0.05). Based on the research results, pregnant women should routinely consume Fe tablets as many as 90 tablets during pregnancy and consume foods containing iron such as green vegetables. officers are expected to increase counseling about Anemia and FE tablets and especially village midwives visit pregnant women's homes to monitor mothers' compliance in consuming Fe tablets at least once a week.